The Effect of Profitability, Leverage, Capital Intensity and Corporate Social Responsibility on Tax Avoidance in Energy Sector Companies Listed on the Indonesian Stock Exchange 2020-2024 - Salsabila, Kurnia; Ahmad Rifa’i; Mediya Destalia (Asosiasi Ahli Administrasi Indonesia, 2026)
Tax avoidance is defined as efforts by taxpayers to minimize their tax liabilities by exploiting legitimate loopholes in tax regulations. Tax avoidance is carried out through tax planning. This study aims to analyze the effect of profitability, leverage, capital intensity, and corporate social responsibility on tax avoidance. Data collection was conducted by documenting data sourced from annual reports published through the Indonesia Stock Exchange and the official websites of energy sector companies from 2020-2024. Sample collection used purposive sampling, resulting in a total of 100 samples consisting of 20 energy companies listed on the Indonesia Stock Exchange from 2020-2024. This study used multiple linear regression with a panel-data approach in Eviews 12. The partial results showed that leverage had a significant effect on tax avoidance, while profitability, capital intensity, and corporate social responsibility did not have a significant effect on tax avoidance. Meanwhile, the simultaneous test results show that profitability, leverage, capital intensity, and corporate social responsibility together have a significant effect on tax avoidance.